Growth, Productivity Behavior and Economics of Castor (Ricinus communis L.) Hybrids as Influenced by Different Fertility Levels under North Gujarat Agroclimatic Region - Jat, A L; Desai, A G (Annals of Arid Zone, 2021)
A field experiment was conducted at Castor-Mustard Research Station, S.D. Agricultural University, Sardarkrushinagar during kharif season of 2016-17 with five castor hybrids (DCH 1720, SHB 896, DCH 177, DCH 519 and GCH 7) grown with three fertility levels (50% RDF, 100% RDF and 150% RDF). Results revealed that among the castor hybrids studied, SHB 896 registered significantly higher number of effective branches plant-1, 100-seed weight, seed yield, oil content, net return, BCR, crop productivity and crop profitability of castor. On other hand, application of 150% RDF gave significantly higher yield attributes, yield and monetary returns i.e. number of branches plant-1, seed yield, oil content, net return, BCR, crop productivity and profitability of castor compared to other fertility levels under Northern Gujarat conditions. Key words: Castor, fertility levels, hybrids, productivity, profitability, yield.